Standardisasi Parameter Spesifik Dan Non Spesifik Ekstrak Etanol Daun Murbei (Morus alba L.) Asal Kabupaten Soppeng Provinsi Sulawesi Selatan - Yuri Pratiwi Utami, Burhanuddin Taebe, Fatmawati (Jurnal Farmasi dan Ilmu Pengobatan, 2016)
Leaves of mulberry (Morus alba L.) is one of the Moraceae family that has long been used as traditional medicine. Empiricallysociety have used of mulberry as a folk remedy for influenza, malaria, hypertension, asthma, hypertension drugs, palpitation, diabetes, insomnia, vertigo, anemia, and Hepatitis. The purpose of this study was establishing a specific and non-specific standards of the ethanol extract of mulberry leaves. The extract was obtained by maceration method using ethanol 70% with rendamen of 19.52%. Specific parameters include organoleptic observations such as, Dark Green color, distinctive smell, and has a bitter taste.Furthermore determine their flavonoids, tannins, steroids, alkaloids. Chromatogram pattern indicates the presence of some stains and Rf values are different. The compound Levels of water-soluble is 0.805%, while compound level of ethanol– soluble is 0.474%. Total ash content is 6.89%. Non–specific parameters include acid insoluble ash content is 1.8575%. The mass of extract specification 1.045 g/mL. Total bacterial contamination eligible extract as much is 10.66 X 10-2 colonies/g, and a total of mold contamination as much is 13.6 X 10-2 and 14,3x10-3 colonies/g